Ultra-Thin AlPO4 Layer Coated LiNi0.7Co0.15Mn0.15O2 Cathodes With Enhanced High-Voltage and High-Temperature Performance for Lithium-Ion Half/Full Batteries - Li, Wei; Yang, Lishan; Li, Yunjiao; Chen, Yongxiang; Guo, Jia; Zhu, Jie; Pan, Hao; Xi, Xiaoming (Frontiers in Chemistry, 2020)
Side-reactions in LiNi1-x-yCoxMnyO2 (0≤-x+y≤1) cathode materials are one kind of the problems that would deteriorate the surface structure and the electrochemical stabilities of the cathodes, especially when they are working at high cut-off voltages and high temperatures. In this study, an ultrathin (~10 nm) AlPO4 coating layer was fabricated through a two-step “feeding” process on LiNi0.7Co0.15Mn0.15O2 (NCM) cathode materials. The structure and chemical composition of the AlPO4 coating were studied by XRD, SEM, TEM and XPS characterizations. Further electrochemical testing revealed that the AlPO4-coated LiNi0.7Co0.15Mn0.15O2 cathode exhibited enhanced electrochemical stabilities in the case of high cut-off voltage at both 25 and 55 °C. In detail, the AlPO4-coated LiNi0.7Co0.15Mn0.15O2 could deliver 186.50 mAh g-1 with 81.5% capacity retention after 100 cycles at 1C over 3-4.5 V in coin cell, far higher than the 71.4% capacity retention of the pristine electrode. In prismatic full cell, the coated sample also kept 89.5% capacity retention at 25 °C and 81.1% capacity retention at 55 °C even after 300 cycles (2.75-4.35 V, 1C), showing better cycling stability than that of the pristine NCM. The ultrathin AlPO4 coating could not only keep the bulk structure stability from the surface degradation, but also diminishes the electrochemical resistance varies after cycles, thereby supporting the coated cathodes with enhanced electrochemical stability.